Longer repetition duration increases muscle activation and blood lactate response in matched resistance training protocols - Hugo Cesar Martins-Costa; Rodrigo Cesar Ribeiro Diniz; Fernando Vitor Lima; Sandra Carvalho Machado; Rafael Silva Valle de Almeida; André Gustavo Pereira de Andrade; Mauro Heleno Chagas (Universidade Estadual Paulista (UNESP), 2016)
Abstract This study analyzed the effect of different repetition durations on electromyographic and blood lactate responses of the bench press exercise. Fifteen recreationally trained male volunteers completed two training protocols, matched for intensity (% one-repetition maximum; 1RM), number of sets, number of repetitions, and rest intervals. One of the protocols was performed with a repetition duration of 4 s (2 s concentric: 2 s eccentric; 2:2 protocol), whereas the second protocol had a repetition duration of 6 s (2 s concentric: 4 s eccentric; 2:4 protocol). The results showed higher normalized integrated electromyography (pectoralis major and triceps brachii) for the 2:4 protocol. Blood lactate concentration was also higher in the 2:4 protocol across all sets. These results show that adding 2 s to the eccentric action in matched training protocols increases muscle activation and blood lactate response, which reinforces the notion that increasing repetition duration is an alternative load progression in resistance training.